TINJAUAN ILMIAH MENGENAI PERBANDINGAN EFEKTIVITAS DAN KEAMANAN ERDOSTEIN, KARBOSISTEIN, DAN N-ASETILSISTEIN PADA PASIEN PENYAKIT PARU OBSTRUKTIF KRONIK EKSASERBASI AKUT - Walter, Bryan; Wiliam, Wiliam; Citraningtyas, Theresia (Jurnal MedScientiae, 2024)
Acute exacerbation of Chronic Obstructive Pulmonary Disease (COPD) is a worsening of stable COPD/respiratory symptoms. The 2020 Global Initiative for Chronic Obstructive Lung Disease (GOLD) shows erdostein, carbocysteine, and n-acetylcysteine can reduce the risk of acute exacerbations in COPD. The aim of this writing is to determine and compare the effectiveness and safety of erdostein, carbocysteine, and n-acetylcysteine in acute exacerbations of COPD. The scientific review takes the form of a literature review by searching for data using books, journals and websites. Sixteen articles were obtained with the results that erdosteine, carbocysteine, and n-acetylcysteine reduced the risk of acute exacerbations of COPD. The best effectiveness results depend on the dose of the drug and the length of use. The best reduction in the risk of exacerbation was oral erdostein, dose 900 mg daily for 10 days (39.1%), Carbocysteine 1500 mg daily for 6-12 months (p < 0.00001) and n-acetylcysteine 1,200 mg/day for 3 months (p<0.05). Erdostein was well tolerated and there were no treatment-related side effects. The frequency of side effects of respiratory tract infections was not detected for erdostein, but for carbocysteine it was found to be 0.56% and NAC 10.85%. Two patients dropped out of the study because of gastrointestinal disturbances related to carbocysteine side effects. The conclusion of this scientific review is that the use of erdostein 900 mg/day for 10 days has the best effectiveness in reducing COPD exacerbations, then carbocysteine 1500 mg/day for 6-12 months, then n-acetylcysteine 1200 mg/day for 3 months.